Taco fiesta a business plan for small scale production of soft taco delights - Guy, Cleobelle Stephanie Daria (2011)
A new fast food chain by the name of Taco Fiesta is about to rise in the market. It is a uique taco company that will sell soft tacos in four major tasty varieties : Beef Chilli Burritos, Taco Grande, Meaty Me Taco, and Taco Ala King. Its main uniqueness aside form being new in the market in Mintal, Davao City is its utilization of banana flour as one of its main ingredients. It is also classified as a Philippine version of the known Mexican soft taco. The main target markets for this company are students, young adults, and people ranging from 14 to 40 years old. Taco Fiesta will be strategically located at the heart of the target markets which is specifically between National Highway and San Francisco Street in Mintal, Davao City. The Taco Fiesta stall will occupy about 6 sq. m. in lot area. This company will employ three staffs and one supervisor or quality control officer. This company will be solely owned by Cleobelle Stephanie Guy. The initial capital and operational for this venture will be Php250,000. Taco Fiesta is expected to launch by June 2011 just in time for the upcoming school year.
Thesis (BS Food Technology) -- University of the Philippines Mindanao, 2011
Keywords: Taco Fiesta; Beef Chilli Burritos; Taco Grande; Meaty Me Taco; Taco Ala King; Banana flour